Edward Sapir’s View About International Auxiliary Language - Kulczycki, Emanuel (Wydawnictwo Instytutu Filozofii UAM, 2008)
The search for common attributes of all languages is connected with the search for characteristics which differentiate languages. If some attributes cannot be found in every language, what is cause of this situation? Is it linked up with the origin of language or with users of the language?
Keywords: Sapir; language; artificial language